Was Trafficking in Persons Really Criminalised? - Kangaspunta, Kristiina (Anti-Trafficking Review, 2015)
This paper examines the successes and setbacks in the criminal justice response to trafficking in persons. While today, the majority of countries have passed specific legislation criminalising human trafficking in response to the United Nations Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children, there are still very few convictions of trafficking. Using currently available knowledge, this paper discusses four possible reasons for low conviction rates. Further, the paper suggests that due to the heavy dependency on victim testimonies when prosecuting trafficking in persons crimes, members of criminal organisations that are easily identifiable by victims may face criminal charges more frequently than other members of the criminal group, particularly those in positions of greater responsibility who profit the most from the criminal activities. In this context, the exceptionally high number of women among convicted offenders is explored.